Different Protocols for Low Whole-Body Vibration Frequency for Spasticity and Physical Performance in Children with Spastic Cerebral Palsy - Punnee Peungsuwan; Uraiwan Chatchawan; Wanida Donpunha; Pisamai Malila; Thanyaluck Sriboonreung (Children, 2023)
Background: Whole-body vibration (WBV) is a therapeutic exercise tool that can be used in children with cerebral palsy (CP). A low vibration frequency with different protocols has been suggested, but no optimal dose has been explicitly indicated. We aimed to determine the superiority of a gradually increased 7–18 Hz WBV protocol over a static 11 Hz WBV and the immediate and short-term effects of WBV training on improving spasticity, functional strength, balance, and walking ability in children with spastic CP. Methods: Twenty-four participants with CP (mean age: 11.5 ± 2.9 years) were randomly allocated into protocols of a static 11 Hz vibration frequency group (SVF) or one that increased from a 7 to an 18 Hz vibration frequency (IVF) (n = 12/group). The WBV programmes were completed for 30 min/session/day to identify immediate effects, and the short-term programme then continued for four days/week for eight weeks. Results: Modified Ashworth Scale scores significantly and immediately improved in the IVF group (hip adductor and knee extensor, p < 0.05), and after eight weeks showed significant improvement in the SVF group (ankle plantar flexor, p < 0.05). Within groups, the Five Times Sit to Stand Test (FTSTS), the Time Up and Go Test and the Functional Reach Test significantly improved in the SVF group, whereas only the FTSTS improved in the IVF group (p < 0.05). There were no significant between-group differences at the eight-week postintervention, except reduced spasticity. Conclusions: A protocol of 7–18 Hz WBV seems to offer superior immediate results in terms of improved spasticity; however, a static 11 Hz protocol appears to offer superior results after eight weeks, although the two protocols did not differ significantly in effects on physical performance. This finding may facilitate preparations to normalise muscle tone before functional mobility therapy. The study results may support future studies about the dose-response of WBV frequency.